Livestock husbandry practices and herd composition influence leopard-human conflict in Pokhara Valley, Nepal. Issue 1 (2nd January 2020) - Adhikari, Bikash; Odden, Morten; Adhikari, Bindu; Panthi, Saroj; López-Bao, José Vicente; Low, Matthew
ABSTRACT: Leopard ( Panthera pardus ) predation on domestic animals is often associated with human-leopard conflict. We investigated leopard predation patterns of domestic animals using a semi-structured questionnaire. We quantified domestic animal losses in randomly selected households ( n = 62) and households with previously reported leopard predation ( n = 33) in the Pokhara region of Nepal from 2014–2016. Leopard predation of livestock was relatively rare (0.6% risk of livestock being taken per year versus 8% chance of death due to disease). The probability of leopard attacks decreased as the proportion of larger stock increased in flocks, and with increasing flock sizes. Several indigenous animal husbandry practices influenced livestock predation patterns by leopards and the level of human tolerance. These include communal ownership of free roaming dogs and mixing flocks of goats with large stock.